2014
DOI: 10.5564/mjc.v15i0.319
|View full text |Cite
|
Sign up to set email alerts
|

Study on synthesizing Mg/Al layered double hydroxides at different pHs

Abstract: Mg/Al layered double hydroxide (LDH) was successfully synthesized at different pHs values. The Mg/AL LDH was well characterized by X-Ray diffraction and Fourier transform infrared analysis. The morphology of the LDH was observed using Scanning electron microscopy with energy dispersive X-ray spectroscopy. The influence of pH values on the morphology of the Mg/Al LDHs were studied. The result showed that the well-synthesized Mg/Al LDHs could be obtained when the pH value was about 10.0 at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[39][40][41] The peaks at 1380.8 and 617.1 cm −1 and the shoulder at 2977.6 cm −1 were attributed correspondingly to the C-O stretching mode of carbonate group, Al-O stretching mode and stretching vibration of carbonate-H 2 O in the interlayer. 36,42,43 Scanning electron micrographs of Mg-Al-LDH were taken using a MIRA3 TESCAN instrument at 15 keV. SEM photos indicated that the surface morphology of Mg-Al-LDH nanocompound and its samples modified with NaOH solutions at pHs of 10, 13 and 14 were aggregation of Mg-Al-LDH particles with a sand rose morphology, The results showed that atomic percentages of magnesium and aluminum on its surface were 18.88 and 6.62% respectively which validated the Mg-Al-LDH formation, Fig.…”
Section: Characterization Of Mg-al-ldhmentioning
confidence: 99%
“…[39][40][41] The peaks at 1380.8 and 617.1 cm −1 and the shoulder at 2977.6 cm −1 were attributed correspondingly to the C-O stretching mode of carbonate group, Al-O stretching mode and stretching vibration of carbonate-H 2 O in the interlayer. 36,42,43 Scanning electron micrographs of Mg-Al-LDH were taken using a MIRA3 TESCAN instrument at 15 keV. SEM photos indicated that the surface morphology of Mg-Al-LDH nanocompound and its samples modified with NaOH solutions at pHs of 10, 13 and 14 were aggregation of Mg-Al-LDH particles with a sand rose morphology, The results showed that atomic percentages of magnesium and aluminum on its surface were 18.88 and 6.62% respectively which validated the Mg-Al-LDH formation, Fig.…”
Section: Characterization Of Mg-al-ldhmentioning
confidence: 99%